Lappaol F regulates the cell cycle by activating CDKN1C/p57 in human colorectal cancer cells - Rui-Yi Yang; Jia-Yi Tan; Zhe Liu; Xiao-Ling Shen; Ying-Jie Hu (Taylor & Francis Group, 2023)
AbstractContext Lappaol F (LAF), a natural lignan from Arctium lappa Linné (Asteraceae), inhibits tumor cell growth in vitro and in vivo. The underlying mechanism involves the suppression of the Yes-associated protein. However, the specific role of LAF in cell cycle regulation remains unknown.Objective This study determined the molecular mechanism by which LAF regulates cell cycle progression.Materials and methods Various colon cancer cell lines (SW480, HCT15, and HCT116) were treated with LAF (25, 50, and 75 μmol/L) for 48 h. The effects of LAF on cell proliferation and cell cycle were determined using sulforhodamine B and flow cytometry assays. Differentially expressed proteins (DEPs) were identified using quantitative proteomics. Bioinformatic analysis of DEPs was conducted via Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Expression levels of DEPs in the cell cycle pathway were analyzed using RT-qPCR and western blotting.Results LAF suppressed the proliferation of SW480, HCT15, and HCT116 cells (IC50 47.1, 51.4, and 32.8 μmol/L, respectively) and induced cell cycle arrest at the S phase. A total of 6331 proteins were identified and quantified, of which 127 were differentially expressed between the LAF-treated and untreated groups. GO and KEGG enrichment analyses revealed that DEPs mainly participated in the cell cycle. CDKN1C/p57 showed the most significant differential expression, with the highest fold-change (3.155-fold). Knockdown of CDKN1C/p57 attenuated the S phase cell cycle arrest and proliferation inhibition induced by LAF.Conclusion LAF exerts antitumor effects via S phase arrest by activating CDKN1C/p57 in colorectal cancer cells.